Öğrenen organizasyon yoluyla işletme stratejilerinin başarısının artırılması - Çam, Salim (My University, 2000)
Organtisations are social systems, which are in a continious alteration. They are categorized due to their characteristics. They are; knowing organizations, understanding organizations, thinking organizations and learning organizations. The subject of this study is the Learning Organization which sprung from the thinking organtization, and increasing the the achievement of management strategies throughout the learning organization. The international competition between several firms lead various strategy alternatives to come to surface. These alternatives are put into practice by many organizations in nearly the same way. Though the organizations shoul develop new strategies due to be successful under these hard conditions of competition. The Learning Organization plays also an important role by increasing the achievement of the organizational strategies called 'generic strategies' by Michael Porter. An organization has to apply four generic strategies to reach its best potential, in it's own industrial area. These are; 1. Cost Leadership strategy 2. Differentiating strategy 3. Focusing strategy 4. Emergent strategy Within the thesis of 'Increasing managent strategies' achievement by the learning organization', many hypothesis' are generated. These hypothesis' have been experimented on a running 'textile firm' and the deductions have supported them to a great extent. The fundamental diagnosises are below. By applying the five basis disciplines of the Learning Organization (Personal Mastery, Systems Thinking, Team Learning, Shared Vision, Mental Models); · The learning degree of the employees is increased to a great extent · The main costs have been decreased · Marketing research studies have been made better and more satisfying as a team · A data base on customer demands has been installed and products and services of higher quality have been served to customers much faster · A shift to new product technologies has been made and the functions of products increased.
Keywords: İşletmeler-Yönetim